PERFORMANCE OF EXOTIC SUGAR BEET VARIETIES UNDER AGRO-CLIMATIC CONDITIONS OF LOWER SINDH - G. M. Kaloi; A. H. Mari; M. Zubair; R. N. Panhwar; N. Bughio; S. Junejo; G. S. Unar; M. A. Bhutto (Journal of Animal and Plant Sciences, 2014)
A comparative study was conducted to assess the performance of ten exotic sugar beet varieties on four locations of lower Sindh. Soils of the experimental locations were clay and clay loam in texture, alkaline in reaction and saline in nature. The experiment was laid out according to a randomized complete block design (RCBD) with three replications.  All sugar beet varieties showed different behavior with respect to beet yield and sugar recovery. Maximum beet yield was produced by SDPAK 03/06 followed by California, Magnolia and SDPAK 09/07. In terms of sugar recovery, the varieties Magnolia, SDPAK 01/07, SDPAK 07/07 and SDPAK 09/07 performed better and were almost at par. While, the varieties California, Magnolia, SDPAK 03/04 and SDPAK 09/07 performed best with regard to beet yield and sugar recovery. The results illustrated that sugar beet can be successfully grown on saline soils of lower Sindh. The sugar beet cultivation on marginal soils will bring more economic returns to growers as compared to cultivation of others especially sugarcane.
Keywords: Sugar beet varieties; beet yield; sugar recovery; climate; saline soils; lower Sindh